Pengembangan Media Pembelajaran Interaktif Sistem Tata Surya untuk Siswa Kelas 6 Sekolah Dasar - Efrianto, Delvia Nova; Famukhit , Muga Linggar; Rahayu , Dwi (Scholarly Journal of Elementary School, 2022)
This study aims to develop learning media for the solar system using Adobe Flash to support the learning process of students at SDN 1 Hadiluwih, help foster interest in learning the solar system through teaching aids that are more attractive and easy to understand, implement learning media based on solar systems. Interactive Adobe Flash. The research method used in this research is the method of research and development (Research & Development). The data collection method used a questionnaire method with the research subjects of grade 6 elementary school students. Processing the questionnaire method with a Likert scale. The data analysis technique uses the help of the Microsoft Excel program. Based on the research results, it can be seen that students are greatly helped in learning the Solar System using interactive learning media. Students are helped in studying the material of the solar system because there are videos, pictures, quizzes, and writing that are easy to understand.